Using theory to better communicate to different audiences about Whooping Crane conservation. Issue 2 (4th March 2021) - Lessard, Sarah K.; Morse, Wayde C.; Lepczyk, Christopher A.; Seekamp, Erin
ABSTRACT: Effective outreach for an endangered species often requires an understanding of human dimensions information to guide pro-conservation behavior. To provide a foundation for outreach communication strategies regarding Whooping Crane conservation in Alabama, we administered surveys to local residents, waterfowl hunters, and birders. We tested a theoretical framework using constructs from the cognitive hierarchy, value-belief-norm theory, emotional dispositions, and knowledge about the species to identify the best predictors of attitudes and behavioral intentions toward the conservation of Whooping Cranes. Regression analyzes revealed that a combination of constructs from these frameworks directly predicted attitudes and behavioral intentions toward Whooping Cranes. Findings demonstrated that the best predictors were different across audiences and different for predicting attitudes and behavioral intentions. Each of the predictor variables from the multiple theories provided explanatory power for both attitudes and behavioral intentions and across all audiences. Outreach can use this information to develop content and audience-specific messaging.